Penerapan Restorative Justice Terhadap Penyalahguna Narkotika Pada Tingkat Penuntutan Berdasarkan Asesmen Terpadu : Studi Di Kejaksaan Negeri Lampung Selatan - Dian Prayoga; Firganefi Firganefi; Sri Riski (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to explore the implementation of restorative justice in handling drug abuse cases at the level of prosecution, focusing on the South Lampung District Attorney's Office. The research methodology includes normative juridical and empirical approaches. The results show that the implementation of restorative justice as an alternative in handling drug abuse cases outside the court has had a positive impact on rehabilitating offenders and preventing imprisonment as a last resort. However, there are still several obstacles to its implementation, such as lack of understanding and coordination among related institutions, as well as insufficient facilities and resources for rehabilitation. Therefore, concerted efforts are needed from various parties to improve understanding, coordination, and the provision of facilities and resources that support the implementation of restorative justice in handling drug abuse cases.